Juvenile Scleroderma: Apropos of Two Cases - Belde Kasap,; Alper Soylu,; Mehmet Türkmen,; Salih Kavukçu, (Archives of Rheumatology, 2007)
Scleroderma is a kind of autoimmune disease characterized by fibrosis and induration, the localized form of which is related only to the skin, while the systemic type is connected with of the other organs. Here, we report one case with localized and another with systemic type of scleroderma both of whom have unusual clinical properties. Case-1: A 19 months-old girl was admitted to our clinic with upper respiratory tract infection findings. By change in her physical examination, a 5 cm scarred area was observed. This was positioned at 1/3 upper thigh. It was learned that the lesion had been present since the age of 15 months. All laboratory findings were in normal ranges other than ANA positivity at 1/40 titer. Skin biopsy revealed plaque morfea and local steroid and vazeline were prescribed. The extention of the lesion was limited with the therapy. Case-2: A 12-year-old girl complained that for the last four months, she had been suffering from shiny skin at her face, hands and feet. In her physical examination, localized edema on the distal parts of her wrists, knees, and face was observed. ANA titer was 1/1280 and anti-centromer antibody was (+). Other laboratory findings and nailfold capillaroscopy were normal. After a low-dose steroid treatment for 8 months, she completely recovered and the medication was stopped. Conclusion: We reported two cases, one with a very early onset of localized scleroderma and another with systemic sclerosis who recovered with low-dose steroid prescribed at the initial phase of the disease. (Rheumatism 2007; 22: 151-5)